Designing a Study on Educational Communication in the New Normal and Digital Era - Prastyanti, Shinta; Sulaiman, Adhi Iman; Adi, Tri Nugroho; Prawoto Jati, Petrus Imam; Wahyuningrat, Wahyuningrat; Yamin, Muhammad; Arimurti, Niken Hapsari (Technium Education and Humanities, 2024)
The 2019 Coronavirus Disease (COVID-19) pandemic has resulted in restrictions across various sectors, including the economy, social activities, tourism, and notably, in the field of education. Therefore, it is imperative to investigate and formulate a design for the study of educational communication in the new normal and digital era. This research employs a qualitative case study methodology, involving data collection through observation, interviews, documentation, and Focus Group Discussions. Informant selection utilizes purposive sampling from prominent schools in Purwokerto City, comprising school foundation executives, primary school principals, primary school teachers, representatives of eleventh or twelfth-grade students, as well as education experts and practitioners. The research analysis utilizes an interactive analysis approach, encompassing data collection, data reduction, verification, triangulation, and conclusion drawing. The findings reveal that educational stakeholders, such as teachers and students in both urban and rural schools, face similar challenges in adapting to the use of online educational media and applications. This difficulty arises from the lack of prior exposure before the onset of the COVID-19 pandemic. Schools, teachers, and students necessitate socialization, adaptation, and the adoption of innovative digital media and technology applications, as exemplified in Electronic Learning (E-Learning). E-Learning is an electronic learning system utilizing computer and internet technologies that support remote learning without the need for face-to-face interactions. The negative impact of using digital media in the educational process during the COVID-19 pandemic includes feelings of monotony, reduced concentration, and diminished humanistic interaction between students and educators, as well as among students themselves due to the absence of direct face-to-face contact. However, the positive impact of employing digital educational media lies in diversifying, enhancing, attracting, and innovating the educational process.